Going Green: Framing Effects in a Dynamic Coordination Game - Reyer Gerlagh; Eline van der Heijden (Center for Economic Studies and ifo Institute (CESifo), 2015)
We experimentally study decision-making in a novel dynamic coordination game. The game captures features of a transition between externality networks. Groups consisting of three subjects start in a stable benchmark equilibrium with network externality. Over seven rounds, they can transit to an alternative stable equilibrium based on the other network. The alternative network has higher payoffs, but the transition is slow and costly. Coordination is required to implement the transition while minimizing costs. In the experiment, the game is repeated five times, which enables groups to learn to coordinate over time. We compare a neutral language treatment with a `green framing' treatment, in which meaningful context is added to the instructions. We find the green framing to significantly increase the number of profitable transitions, but also to inhibit the learning from past experiences, and thus it reduces coherence of strategies. Consequently, payoffs in both treatments are similar even though the green framing results in twice as many transitions. In the context of environmental policy, the experiment suggests general support for `going green', but we also find evidence for anchoring of beliefs by green framing; proponents and opponents stick to their initial strategies.
Keywords: C73; C92; O44; 330; cost of transition; lab experiment; dynamic stag hunt game; framing